Craniosynostosis of Coronal Suture in Twist1+/− Mice Occurs Through Endochondral Ossification Recapitulating the Physiological Closure of Posterior Frontal Suture - Behr, Bjorn; Longaker, Michael T.; Quarto, Natalina (Frontiers in Physiology, 2011)
Craniosynostosis, the premature closure of cranial suture, is a pathologic condition that affects 1/2000 live births. Saethre-Chotzen syndrome is a genetic condition characterized by craniosynostosis. The Saethre-Chotzen syndrome, which is defined by loss-of-function mutations in the TWIST gene, is the second most prevalent craniosynostosis. Although much of the genetics and phenotypes in craniosynostosis syndromes is understood, less is known about the underlying ossification mechanism during suture closure. We have previously demonstrated that physiological closure of the posterior frontal (PF) suture occurs through endochondral ossification. Moreover, we revealed that antagonizing canonical Wnt signaling in the sagittal suture leads to endochondral ossification of the suture mesenchyme and sagittal synostosis, presumably by inhibiting Twist1. Classic Saethre-Chotzen syndrome is characterized by coronal synostosis, and the haploinsufficient Twist1+/- mice represents a suitable model for studying this syndrome. Thus, we seeked to understand the underlying ossification process in coronal craniosynostosis in Twist1+/- mice. Our data indicate that coronal suture closure in Twist1+/- mice occurs between postnatal day 9 to 13 by endochondral ossification, as shown by histology, gene expression analysis and immunohistochemistry. In conclusion, this study reveals that coronal craniosynostosis in Twist1+/- mice occurs through endochondral ossification. Moreover, it suggests that haploinsufficency of Twist1 gene, a target of canonical Wnt-signaling, and inhibitor of chondrogenesis, mimics conditions of inactive canonical Wnt-signaling leading to craniosynostosis.